A Pilot Study of Interpersonal Psychotherapy for PTSD in Women Veterans. Issue 1 (2nd January 2016) - Krupnick, Janice L.; Melnikoff, Elizabeth; Reinhard, Matthew
Abstract : Objective : This pilot study aimed to determine whether interpersonal psychotherapy (IPT) for posttraumatic stress disorder (PTSD) would be effective with a sample of women veterans who experienced military-related PTSD. Method : Women veterans presenting for mental health services through the Trauma Services Program at the Washington, DC, Veterans Affairs Medical Center (VAMC) were referred to the study by Veterans Affairs (VA) clinicians if they experienced trauma during their military service and scored > 35 on the PTSD Checklist–Military Version. A total of 20 women completed a baseline assessment and were referred to treatment, the first trial of this treatment method with a veteran sample. Of the 15 women veterans who started treatment, 10 completed a trial of 12 individual sessions. Assessments were conducted posttreatment and at three months posttreatment follow-up. Results : There was a significant decline in PTSD symptom severity from baseline to posttreatment, and these gains were maintained at three-month follow-up. Approximately one-third of the group no longer met full criteria for PTSD diagnosis, results that are comparable to studies of evidence-based treatments for PTSD (prolonged exposure and cognitive processing therapy) in military samples. Conclusions : IPT, a non-trauma-focused intervention that aims to increase social support and improve interpersonal functioning, shows promise as another means of addressing PTSD in veterans. It should be tested in a larger sample to determine if IPT for PTSD might serve as an alternative for veterans who would prefer a non-trauma-focused intervention to address their difficulties.